Rediscovery of fossils from the middle gravels and lower loam at Barnfield Pit, Swanscombe, Kent (UK). (December 2020) - Key, Alastair; Deter, Chris; Muthana, Angela; Dolding-Smith, Jessica; McFarlane, Gina; Mahoney, Patrick
Highlights: Faunal fossils from the hominin levels at Barnfield Pit have been rediscovered. Recovered between 1951 and 55 by John Carreck, they remained unknown until now. Their recovery was informal and undertaken in-between John Wymer's excavations. There is potential for other fossils from the 'Carreck Collection' to be rediscovered. Abstract: Swanscombe is the most important early human fossil site in the UK, and one of the richest locations for Middle Pleistocene fauna. Famed for three 400, 000-year-old hominin skull fragments recovered from Barnfield Pit between 1935 and 1955, the site is now legally protected and has not seen substantial excavation for decades. New fossil material from Swanscombe is fleetingly rare. Here we report the rediscovery of a collection of fossils recovered from Barnfield Pit between 1951 and 1955 by John Carreck. The 'Carreck Collection' includes multiple mammalian fossils from the hominin fossil and artefact-bearing Middle Gravels and Lower Loam. Detailed notes contained in the collection reveal that most were recovered prior to John Wymer's discovery of the third hominin skull fragment on the 30th of July 1955. Several, however, were collected in the months immediately after this, including at least two fossils recovered from the 'New Skull Site' on the 3rd of August 1955. Given their provenance and the nature of their discovery, these fossils are of significance to the history of British human origins research. Only a portion of the Carreck Collection, however, is currently accounted for. There is potential, therefore, for other fossils from Barnfield Pit to be rediscovered, including those with significance to our understanding of human prehistory in the UK.